World Investment Report 2017 - Conference des Nations Unies sur le commerce et le développement (United Nations, 2017)
The annual World Investment Report presents foreign direct investment (FDI) trends and prospects at global, regional and national levels. It also analyses the latest developments in new policy measures for investment promotion, facilitation and regulation around the world, and provides the annual update on investment treaties, their reform and investment dispute settlement cases. The 2017 edition, subtitled